2020
DOI: 10.3389/fimmu.2020.00804
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neutrophil Populations in the Spleen During PICS

Abstract: While mortality after acute sepsis has decreased, the long-term recovery for survivors is still poor, particularly those developing persistent inflammation, immunosuppression, and catabolism syndrome (PICS). While previously thought that activated neutrophils responding to the acute phase of sepsis migrate to the spleen to undergo cell death and contribute to immunosuppression, our data show a significant accumulation of distinct, yet functional, neutrophil populations in the spleen in a murine model of PICS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…As described above, we assessed the contribution of neutrophil subtypes to ROS production. We confirm previous results 23 by showing that the mature CD62L-/ICAM-1 + and CD62L + /ICAM-1 + phenotypes contribute the most to ROS production (Fig. 3 A).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As described above, we assessed the contribution of neutrophil subtypes to ROS production. We confirm previous results 23 by showing that the mature CD62L-/ICAM-1 + and CD62L + /ICAM-1 + phenotypes contribute the most to ROS production (Fig. 3 A).…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we and others depicted that the CD62L-/ICAM-1 + phenotype can be considered mature and shows increased functionality compared to other phenotypes (Fig. 3 A) 18 , 23 . Therefore, we interpret the observed effect of neutrophils being compromised in their activation as an impairment of proper immune activation and not a prevention of excessive inflammation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It is known that neutrophils exhibit highly different phenotypes and functions mainly depending on tissues and individual conditions [22][23][24][25]. Though studies reported neutrophil subpopulation/heterogeneity in the blood, bone marrow, spleen, and even in the brain, lung, and gut [26][27][28], the kidney neutrophil has been rarely studied for its extremely low frequency in this tissue. This study reported neutrophil heterogeneity in ccRCC, comparing with it in healthy condition, in a single-cell level.…”
Section: Discussionmentioning
confidence: 99%